Mesoporous silica-modified upconversion biosensor coupled with real-time ion release properties for ultrasensitive detection of Staphylococcus aureus in meat. (March 2023) - Ouyang, Qin; Zhang, Mingming; Yang, Yongcun; Din, Zia-ud; Chen, Quansheng
Abstract: Staphylococcus aureus ( S. aureus ) is a pathogenic bacterium that can cause serious contamination in meat. Herein, a novel fluorescence biosensor was designed for the rapid detection of S. aureus based on mesoporous silica-modified upconversion nanoparticles (UCNPs-mSiO2 ). Particularly, the mesoporous silica (MS) was introduced to empower the biosensor with hydrophilic and ion loading capabilities. The results showed that the introduction of S. aureus in the system led to the discharge of Fe 2+ ions by binding to the molecular gating (aptamer) of mesoporous channels. The oxidation of Fe 2+ to Fe 3+ in the presence of hydrogen peroxide, resulted in quenching of the fluorescence of UCNPs. Remarkably, the prepared biosensor achieved low detection limits of 25 CFU/mL and a wide detection range of 63–6.3 × 10 6 CFU/mL. The recovery of S. aureus in meat was 91–93% (pork) and 96–105% (beef), which exhibited insignificant difference compared with the traditional plate counting method. Consequently, with its advantages of sensitivity and speed, the developed biosensor can be a promising platform for S. aureus detection in meat. Graphical abstract: Image 1 Highlights: A new biosensor for the detection of S. aureus was developed. Mesoporous silica coated UCNPs were synthesized for ion real-time release. Fe 2+ was released from the mesopores structure and oxidized to Fe 3+ by H2 O2 . Fe 3+ quenched the fluorescence in the sensor system via photoinduced electron transfer. The biosensor was successfully applied for the S. aureus detection in real samples.